ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012- 2015) - Hendra Bagus Yulipratama; Ronny Malavia Mardani (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of this research is to know the Influence of Profitability, Leverage, Company Size To Company Value. The sample in this research is a mining company listed on the Indonesia Stock Exchange listed on the stock exchanges of Indonesia 2012-2015 purposive sampling. Technique of data analysis in this research use multiple regression analysis. Dependent variable in this research is firm value and independent variable is profitability, leverage, and company size The result of research show that profitability and leverage have an effect on company value, while firm size does not have an effect on company value. For further research is expected to add to the category of the company used as sample research, and add other variables that may affect the value of the company. Keywords : Profitability, Leverage, Company Size, Corporate Value.